Geospatial Variability Analysis of Fluoride Quantification in Underground Aquifers of Central Parts of Haryana State, India - Bhardwaj, P.; Awasthi, A.; Singh, J. (Journal of Scientific Research, 2021)
The elevated levels of fluoride in underground water enhance the prevalence of the fluorosis epidemic in Haryana state. To assess the groundwater geospatial variability of fluoride at different depths in central parts of Haryana, the present study has been explored. The samples at eight sites were collected in triplicate at 3 depth levels viz. a) < 10 m below ground level (bgl), b) 10-40 m bgl, and c) > 40 m bgl. Fluoride levels have been determined by the SPADANS-zirconyl oxychloride method using UV-VIS spectrophotometer (Systronics-118). The fluoride concentration varies from 0.19 mg/L to 2.87 mg/L. More than 38 percent of samples exceed the standard prescribed limit of 1.0 mg/L fluoride in drinking water. Fluoride contamination increases in post-monsoon samples with maximum concentration at 40 bgl depth. Due to geological factors (fluoride-bearing minerals in basement rocks) and human-induced (brick-kiln industries, phosphatic fertilizers) factors, a high concentration of fluoride in groundwater is observed. Sustainable defluoridation techniques and a good diet (calcium & vitamin c enriched) can control the adverse effects of fluorosis.